Digital Transformation of Public Sector Accounting: A Literature Review on Technology Adoption in Government Financial Reporting - Irmawati, Irmawati; Haliah; Nirwana (Invoice : Jurnal Ilmu Akuntansi, 2025)
The digital era has transformed public sector accounting, offering opportunities to enhance the quality, transparency, and accountability of government financial reporting through technologies such as artificial intelligence, blockchain, big data analytics, and cloud computing. Despite its potential, research gaps remain regarding the adoption and implementation of these technologies within the public sector. This study aims to examine the development of digital technology in government financial reporting, identify key challenges, and evaluate the impact of emerging technologies on accounting transformation. Using a qualitative approach, a systematic literature review was conducted covering studies published between 2020 and 2025 in Scopus, Web of Science, Google Scholar, and ScienceDirect. Thematic analysis was employed to identify patterns and trends. The findings highlight that technology adoption enhances efficiency, participation, and accountability but faces barriers such as system incompatibility, limited technical capacity, regulatory misalignment, and organizational resistance. The study concludes that digital transformation creates a disruptive yet strategic opportunity for public sector accounting, requiring a gradual and holistic approach. Policy implications include the need for regulatory harmonization, sustainable infrastructure investment, capacity-building programs, and a clear roadmap for technology adoption. This research contributes to the literature by providing an integrated framework for understanding digital transformation in government financial reporting.